1995
DOI: 10.1099/13500872-141-10-2529
|View full text |Cite
|
Sign up to set email alerts
|

Response of the bvg regulon of Bordetella pertussis to different temperatures and short-term temperature shifts

Abstract: Bordetella pertussis produces a number of virulence factors whose expression is coordinately regulated by the bvgA3 locus. Transcription of virulence genes is repressed by environmental factors such as low temperature (25 "C) and chemical stimuli. Temperature shift of bacterial cultures from 25 "C to 37 "C activates two classes of bvg-regulated virulence genes: the early genes, which are activated within 10 min, and late genes, which require 2 4 h for activation. During the interval between the activation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 26 publications
(15 reference statements)
1
40
0
Order By: Relevance
“…Since B. pertussis appears to survive only in the human airway, it may have evolved to link growth phase and virulence with changing conditions in different locations of this restricted environment or during different stages of infection. Prior studies have suggested that Bvg-regulated expression of virulence factors may occur in a temporally or spatially defined sequence (10,30). A possible model for the B. pertussis infectious cycle consists of elaboration of adhesins, toxins, and other virulence factors during early stages of infection, thus permitting colonization, evasion of host immunity, and acquisition of nutrients, followed by declining virulence factor production when bacteria reach high densities and have depleted locally available nutrients.…”
mentioning
confidence: 99%
“…Since B. pertussis appears to survive only in the human airway, it may have evolved to link growth phase and virulence with changing conditions in different locations of this restricted environment or during different stages of infection. Prior studies have suggested that Bvg-regulated expression of virulence factors may occur in a temporally or spatially defined sequence (10,30). A possible model for the B. pertussis infectious cycle consists of elaboration of adhesins, toxins, and other virulence factors during early stages of infection, thus permitting colonization, evasion of host immunity, and acquisition of nutrients, followed by declining virulence factor production when bacteria reach high densities and have depleted locally available nutrients.…”
mentioning
confidence: 99%
“…The cup gene clusters of genes were described as poorly expressed under laboratory conditions (37) and are regulated by a complex regulatory network involving the HNS-like protein MvaT, acting in a phase-variable manner (38) as a transcriptional repressor for cupA (37) and, to a lesser extent, for cupB and cupC (37). A two-component regulatory system, namely, the RocS1 (the sensor of the Roc1 [regulation of cup 1] system)-RocRRocA1 system, homologous to the BvgS-BvgR-BvgA system of Bordetella pertussis (26,39), which controls a number of virulence factors in this bacterium (13), has recently been identified as controlling cupB and cupC gene cluster expression (20). The overproduction of the regulator RocA1 or the sensor RocS1 is sufficient to observe the overexpression of cupB-lacZ and cupC-lacZ transcriptional fusions.…”
mentioning
confidence: 99%
“…Studies have shown that virulence factor expression is influenced by temperature, pH, glutamate levels, free fatty acids, and environmental compounds like nicotinic acid and SO 4 2Ϫ (15,16,23,25,26,35,37,56). Addition of heptakis-(2,6-Odimethyl)-␣-cyclodextrin to the medium increases Ptx yields significantly (15,16,58).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of the vir regulon in B. pertussis is affected by diverse environmental signals (31,32,35). The presence of sulfate anion (SO 4 2Ϫ ) or nicotinic acid (31,32) or growth at low temperature (37) results in decreased expression of ptx and other virulence genes. Naturally occurring BvgS mutants (49), site-directed mutants (34), and serum-resistant mutants (12) have been shown to be less sensitive to these environmental signals.…”
mentioning
confidence: 99%